CARDIAC PATHOPHYSIOLOGY: MECHANISMS, CLINICAL IMPLICATIONS, AND THERAPEUTIC PERSPECTIVES - Khayrullayeva Maftuna Ibodullaevna (Web of Journals Publishing, 2025)
Cardiac pathophysiology encompasses structural, functional, and biochemical alterations in the heart that lead to cardiovascular diseases (CVDs). This paper provides a comprehensive review of myocardial remodeling, ischemia, arrhythmogenesis, and neurohormonal regulation, highlighting their contribution to heart failure, myocardial infarction, and arrhythmias. Using experimental, clinical, and imaging studies, the article emphasizes the interplay between cellular signaling, ion channel dysfunction, and systemic regulation. Understanding these mechanisms provides insights into developing targeted therapies and improving patient outcomes.
Keywords: Cardiac pathophysiology, myocardial remodeling, heart failure, arrhythmia, ischemia, neurohormonal regulation.